Regulatory Pathways for Smart Grid Development in China - Brunekreeft, Gert; Luhmann, Till; Menz, Tobias; Müller, Sven-Uwe; Recknagel, Paul (Springer Nature, 2015)
Energy Policy, Economics and Management; Energy Technology; Environmental Law/Policy/Ecojustice